2020
DOI: 10.2147/ott.s214514
|View full text |Cite
|
Sign up to set email alerts
|

<p>Icariin Mitigates the Growth and Invasion Ability of Human Oral Squamous Cell Carcinoma via Inhibiting Toll-Like Receptor 4 and Phosphorylation of NF-κB P65</p>

Abstract: Background: Oral squamous cell carcinoma (OSCC) is an aggressive malignancy worldwide. Icariin (ICA), an active ingredient of flavonoids, has been demonstrated to possess antitumor activity in diverse cancers. Whereas, the role of ICAin OSCC is still unclear. Methods: Herein, we investigated the anti-tumor effects of ICA in vitro and in vivo. CCK-8, colony formation and trans-well assay were used to examined viability, proliferation and invasion in SCC-9 and SCC-15 cell lines, respectively. Next, we tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… 191 Icariin exhibited antiangiogenic effects in xenograft models of tumors including hepatocellular carcinoma and renal cell carcinoma, 192 and suppressed tumor cell migration and invasion by regulating the Rac1-dependent vasodilator-stimulated phosphoprotein (VASP) pathway. 193 Icariin also enhanced the effects of antineoplastic drugs and radiation therapy; in one study, the combination of icariin and gemcitabine resulted in an enhanced antitumor effect compared to either drug alone, 194 highlighting its therapeutic potential for cancer treatment.…”
Section: Therapeutic Mechanisms Of Icariin In Nervous System Diseases: Literature Review and Network Pharmacology Analysismentioning
confidence: 99%
“… 191 Icariin exhibited antiangiogenic effects in xenograft models of tumors including hepatocellular carcinoma and renal cell carcinoma, 192 and suppressed tumor cell migration and invasion by regulating the Rac1-dependent vasodilator-stimulated phosphoprotein (VASP) pathway. 193 Icariin also enhanced the effects of antineoplastic drugs and radiation therapy; in one study, the combination of icariin and gemcitabine resulted in an enhanced antitumor effect compared to either drug alone, 194 highlighting its therapeutic potential for cancer treatment.…”
Section: Therapeutic Mechanisms Of Icariin In Nervous System Diseases: Literature Review and Network Pharmacology Analysismentioning
confidence: 99%
“…Recently, Hao et al observed that ICA can significantly induce antitumor immunity in murine B16F10 melanoma and MC38 colorectal tumors mice in a CD8 T-cell-dependent way [ 19 ]. In addition, ICA has been demonstrated to attenuate the growth and invasion ability of Human oral squamous cell carcinoma in vitro and in vivo by inducing the down-regulation of Toll-Like Receptor 4 (TLR4)/ NF-κB pathway [ 20 ]. Also, Huang et al demonstrated that ICA inhibited the growth of HeLa cervical cancer cells dose-dependently via inhibiting the mTOR/PI3K/AKT signaling cascade [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In OSCC, in addition to increased TLR4 expression, the distribution of TLR4 likewise increased from the basal hominins to the spiny layer. 215 , 216 In addition, several researchers have suggested that TLR4 overexpression promotes OSCC development and proliferation and is closely associated with poor invasion and metastasis in oral cancer patients. 217 , 218 , 219 , 220 , 221 , 222 These findings demonstrated a strong correlation between TLR4 and the onset and progression of OSCC.…”
Section: Tlr‐related Diseasesmentioning
confidence: 99%